An Analysis Of Translation Method From Indonesia to English in Indonesian Songs “ Bertaut” Covered By Emma Heeters - Agnes Foneria Zebua; Agustina Rotua Purba; Hiskia Frende Purba; Susi Santrika Sitinjak (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This journal examines Emma Heesters' English versions of Indonesian songs, concentrating on the strategies and procedures she employs when translating verses from Indonesian to English, using Diminish Newmark's (1988) interpretation hypothesis as a foundation for evaluation. By analyzing a selection of songs, the study outlines how Heesters addresses social nuances, colloquial expressions, and enthusiasm. This evaluation not only exposes the difficulties involved in interpreting melody verses, but it also emphasizes the significance of maintaining the aesthetic substance of the original piece. Finally, the study improves understanding of interpretation processes in the field of music and cross-cultural contact.